NONSPECIFIC SPONDYLODISCITIS IN ADULTS: RETROSPECTIVE STUDY - ZARZA,WILLIAM (2020)
ABSTRACT Objective To describe the epidemiological and clinical characteristics of patients with pyogenic spondylodiscitis treated in a Brazilian hospital. Methods This is a retrospective study of patients diagnosed with nonspecific spondylodiscitis. Patients of both sexes, above 18 years of age with a minimum follow-up time of 6 months were included. Epidemiological, laboratory, and clinical data were analyzed. Results Nine patients were included. The mean age was 64 years, with seven men (77.7%) and two women (22.2%). All patients evaluated had back pain. The most affected location was the lumbar spine (44.4%). Only three patients (33.3%) had fever and five (55%) had constitutional symptoms. The mean duration of symptoms before diagnosis was 2.5 (± 1.5) weeks. Only four patients (44.4%) had positive cultures. As for neurological status, five patients (55.5%) presented neurological change. At the end of treatment, two patients improved one level in the Frankel score and two patients improved two levels. The main indication for surgery was neurological deficit (55.5%). Two of the patients evaluated died as a result of an infectious condition. Conclusions Less than half of the patients with pyogenic spondylodiscitis had fever or constitutional symptoms. Back pain was present in all cases. In less than half of the patients it was possible to isolate the responsible microorganism. Most patients underwent surgical treatment, although not all improved from the neurological deficit. Level of evidence II; Retrospective study.